Clinoform geometry, geomorphology, facies character and stratigraphic architecture of a sand-rich subaqueous delta: Jurassic Sognefjord Formation, offshore Norway - Patruno,S; Hampson,GJ; Jackson,CA-L; Dreyer,T (Sedimentology, 2015)
The integration of core sedimentology, seismic stratigraphy and seismic geomorphology has enabled interpretation of a sand-prone subaqueous delta in the Upper Jurassic Sognefjord Formation of the Troll Field, Horda Platform, offshore Norway. Mud-prone subaqueous deltas characterised by a compound clinoform morphology are common in many modern tide- and wave-influenced settings, but ancient examples are rarely reported. The Sognefjord Formation data therefore demonstrate the criteria for recognition of subaqueous deltas in the stratigraphic record, as well as refining the depositional model of the main reservoir in the super-giant Troll oil and gas field. Two 10-60 m thick, wave-dominated, regressive-transgressive packages bounded by major marine flooding surfaces are distinguished in the lower Sognefjord Formation. Each regressive-transgressive package corresponds to a set of seismically resolved, westerly-dipping clinoforms, and its bounding surfaces form the seismic “envelope” of a clinoform set. The packages thicken westwards, until they reach a maximum where the clinoform “envelope” rolls over to define a topset-foreset-toeset geometry at the position of maximum regression. Both individual clinoforms and reflections bounding the clinoform sets are oriented sub-parallel to the edge of the Horda Platform (N005-N030). In the eastern half of the field, individual clinoforms are relatively gently dipping (1°-6°) and bound thin (10-30 m) clinothems dominated by fine-grained, hummocky cross-stratified sandstones. Towards the west, clinoforms gradually become steeper (5°-14°) and bound thicker (15-60 m) clinothems that comprise medium-grained, cross-bedded sandstones in their upper parts. Topsets are consistently well developed, except in the westernmost area, where some clinoform foresets are top-truncated. No evidence of subaerial exposure is observed. We interpret deposition by fully subaqueous, near-linear clinoforms that pro